Price premium for foreign shares listed on the stock exchange of singapore - Yew, Guey Hoon (2014)
Since the introduction of Foreign tranche shares for non-residence Singaporean investors in the Stock Exchange of Singapore, the foreign tranche shares are sold at a premium over their respective local counterparts. This paper intends to examine whether the price differential that has prevailed since the foreign tranche was introduced in Singapore can be explained by the plausible differences in risk profile , liquidity and required rate of return of the local and foreign tranche shares. This study on the price behaviour has important implication which may be valuable for investors, regulators, and policymakers involved in equity markets in developing countries .